The family Carditidae (Bivalvia) in the early Danian of Patagonia (Argentina) - Perez, Damián (2017)
The first systematic analysis of the Danian carditids of Patagonia is presented, which includes four genera—one new genus and the first records of three other genera in South America. They consist of Claibornicardia paleopatagonica (Ihering, 1903), a widely distributed species occuring in the Jagüel, Roca and Salamanca formations (Neuquén, Río Negro and Chubut Provinces); Rotundicardia Heaslip, 1968, represented by the new species R. mariobrosorum n. sp., which is restricted to the Roca Formation (Río Negro Province); Cardites feruglioi (Petersen, 1846) (Roca and Lefipán formations, Río Negro and Chubut Provinces); and by Kalelia new genus, which includes K. burmeisteri (Böhm, 1903) from the Salamanca and Roca formations (Río Negro and Chubut Provinces), which is related to the Paris Basin species K. multicostata (Lamarck, 1806) n. comb. and K. pectuncularis (Lamarck, 1806) n. comb. ‘Venericardia’ iheringi (Böhm, 1903), a species known only from internal molds, is described and regarded as a carditid with uncertain affinities. The presence of Claibornicardia, Rotundicardia, and Cardites in Patagonia constitutes the most ancient record of these genera and confirms biogeographical connections previously established between the Danian Argentinian and North American/European fossil faunas.